Determination and correlation of solubility of 4′-bromomethyl-2-cyanobiphenyl in acetone + (ethanol, n-propanol, n-butanol) mixtures. (November 2016) - Xiao, Liping; Wang, Yongli; Yang, Jingxiang; Yuan, Fuhong; Jiang, Chen; Hou, Baohong; Xie, Chuang
Highlights: The solubility of OTBNBr were determined in three kinds of binary solvents. Three model were used to correlate the solubility data. The Akaike's Information Criterion ( AIC ) was used to choose the best mode. Abstract: The solubility of 4′-bromomethyl-2-cyanobiphenyl (OTBNBr) in binary solvent mixtures of acetone + (ethanol, n-propanol, and n-butanol) was experimentally determined within the temperature range 278.15–313.15 K by using a gravimetrical method under atmospheric pressure ( P = 0.1 MPa). The results show that the solubility of OTBNBr monotonously increases with increasing temperature and increasing mole fraction of acetone. The solubility of OTBNBr was correlated by the modified Apelblat equation, the van't Hoff equation, and the CNIBS/R-K model. The Akaike's Information Criterion ( AIC ) was used to choose the best model for correlating the solubility of OTBNBr. The preferred model is the modified Apelblat equation which has the lowest AIC value. Furthermore, the mixing thermodynamic properties (enthalpy, entropy, and Gibbs energy) of OTBNBr were also calculated in the selected solvent mixtures.